VD_FINDINFO Jug / 2015 / 382 vom 13. März 2015 - VD Tribunal cantonal (2015)
APPRÉCIATION DES PREUVES, PRÉSOMPTION D'INNOCENCE, FIXATION DE LA PEINE, TORT MORAL, MENACEDROIT PÉNAL | 47 CO, 180 CP, 47 CP, 10 CPP (CH)